Atividade larvicida de produtos naturais e avaliação da susceptibilidade ao inseticida temefós no controle do Aedes aegypti (Diptera: Culicidae) - Guarda, Carin; Lutinski, Junir Antonio; Roman, Walter Antônio [UNESP]; Busato, Maria Assunta (My University, 2016)
The use of isolated extracts and substances derived from medicinal plants is an alternative to the synthetic insecticides for the population control of insects. In this study, we assessed the larvicidal potential of the flavonoid rutin and of the aqueous extracts of Heteropterys aphrodisiaca O. Mach. (Malpighiaceae), Casearia sylvestris Sw. (Flacourtiaceae), Solidago chilensis Meyen (Asteraceae) and Eugenia uniflora O. Berg. (Myrtaceae) on larval stages of the mosquito Aedes aegypti. The susceptibility of this insect to the insecticide temephos was also investigated. Aqueous extracts of the plants and rutin solution were prepared at concentrations of 125, 250, 500, 750 and 1000μg·ml-1 (n=3). The tests were performed in test tubes containing 60ml of each treatment, where 9 larvae of A. aegypti belonging to the 2nd and 3rd stages were inserted. The results obtained after 24 and 48h were submitted to variance analysis (ANOVA) and Duncan test (p<0.05). The treatment with H. aphrodisiaca at 500μgml-1 showed 100% larvicidal effect in 24h, whilst the efficiency was 21% at 250μgml-1. The treatment with rutin 750μg·ml-1 showed 97% efficiency. The A. aegypti population showed total susceptibility temephos at 0.1, 0.09, 0.08 and 0.07g·l-1. The larvicidal effect of H. aphrodisiaca is a promising outcome and opens pathways for new studies focused on isolation and test of the bioactive compounds of this plant species. The efficiency of rutin makes it an option for use in vector control programs against A. aegypti.
Larvicidal activity of natural products and assessment of susceptibility to the insecticide temefós in controlling the Aedes aegypti (Diptera, Culicidae)